Basic Principles of Electrospinning, Mechanisms, Nanofibre Production, and Anticancer Drug Delivery. (11th April 2022) - Odularu, Ayodele Temidayo
Abstract : Electrospun nanofibres are environmentally friendly compounds, when compared with other approaches of manufacturing nanofibres. This study reviews an easy and simple approach process of producing nanofibres called electrospinning. This review further gives an overview and successful methodical approaches to obtain electrospun (ES) nanofibres appropriate for anticancer drug delivery. The properties and characterization of electrospun nanofibres were reported to confirm successful nanofibre production. The application of characterized ES nanofibres is to deliver the anticancer drug to the right target in the human body. The implication of this study is the application of some of the merits of ES nanofibres (biocompatability, biodegradability, low-cost production, small pore size, and ability to transport anticancer drug to the target cell or organ) to overcome the challenges experienced in the use of anticancer chemotherapeutic agents.